Stadt und Natur — Dichotomie, Kontinuum, soziale Konstruktion? - Chilla, Tobias (Raumforschung und Raumordnung | Spatial Research and Planning, 2005)
The concepts “City” and “Nature” are used as contrasts both in habitual language and in urban research discourses. At the same time there exist multifaceted conjunctions between these seemingly dichotomous categories: planning of municipal parks, research in urban ecology, and debates on urban sustainability are just some examples. While approaching the relationship of city and nature, urban research claims that temporarily valid understandings of nature are nothing given. Nature, especially in urban spaces, is hardly ever pristine and self-acting. Rather, the understanding and the use of “Nature” is strongly associated to societal preferences, to Zeitgeist, and to ever changing frameworks.The article at hand first illustrates and resumes these conjunctions, before it outlines the discussion on the “social construction of nature”. This evolving research approach aims to consider these aspects on a conceptual level.